2020
DOI: 10.1002/cptx.99
|View full text |Cite
|
Sign up to set email alerts
|

Using Human Primary Foreskin Fibroblasts to Study Cellular Damage and Mitochondrial Dysfunction

Abstract: Isolation and maintenance of human primary foreskin fibroblasts (FSK) Basic Protocol 2: Determination of cell viability by crystal violet staining Basic Protocol 3: Transmission electron microscopy to study cellular damage and mitochondrial dysfunction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…HFF is a type of fibroblasts derived from foreskin tissues discarded after surgery. They have been used or proposed to use in several areas of research and medicine, including uses in cellular damage and mitochondrial dysfunction tests of toxins, feeder cells for stem cells, and wound healing [31][32][33][34]. Our data indicated that HUMSCs-MVs effectively reduced formation of hypertrophic scar tissues probably through inhibiting proliferation and invasion of fibroblasts, resolving inflammation and oxidative stress, suppressing Smad2/3 activation, and reducing angiogenesis.…”
Section: Introductionmentioning
confidence: 72%
“…HFF is a type of fibroblasts derived from foreskin tissues discarded after surgery. They have been used or proposed to use in several areas of research and medicine, including uses in cellular damage and mitochondrial dysfunction tests of toxins, feeder cells for stem cells, and wound healing [31][32][33][34]. Our data indicated that HUMSCs-MVs effectively reduced formation of hypertrophic scar tissues probably through inhibiting proliferation and invasion of fibroblasts, resolving inflammation and oxidative stress, suppressing Smad2/3 activation, and reducing angiogenesis.…”
Section: Introductionmentioning
confidence: 72%
“…Primary human dermal fibroblasts (isolated from healthy male neonatal foreskin tissues; Protocol number IRB 120/63 approved by the Institutional Review Board of the Faculty of Medicine, Chulalongkorn University) were grown in Dulbecco’s Modified Eagle Medium (DMEM) (Gibco, Life Technologies, Ltd., Paisley, Scotland, UK) supplemented with 10% fetal bovine serum (FBS) (Gibco, Life Technologies, Ltd.) in a humidified atmosphere at 37°C, 5% CO 2 . The primary human dermal fibroblasts (1 × 10 5 cells/well) in 12-well culture plates were incubated with either the Pseudomonas planktonic bacteria (1 × 10 4 CFU) or the sessile form, prepared by 1 × 10 4 CFU of bacteria on the polystyrene plates, at 37°C in the CO 2 incubator for 6 h. The protocol of primary fibroblasts isolation from a publication was followed [ 62 ]. Briefly, the foreskin tissues from healthy volunteers (IRB 120/63) were collected in sterile containers supplemented with DMEM and 10% FBS with 5 µg/mL of Plasmocin (the mycoplasma elimination reagent) (InvivoGen, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Foreskin cells have shown the ability to develop into a stable cell line of any of the three embryonic germ layers under in vitro conditions [3,4]. In addition, foreskin cells have been shown to be useful as a model for studying cellular damage and mitochondrial disfunction [5,6]. Moreover, the foreskin has been shown to be a good source for mesenchymal stromal cells that have several immunotherapeutic applications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%